Hemangiosarcoma Associated with Polypropylene Suture in a Cat - Corgozinho, Katia Barão; Caloeiro, Cristiane Belchior; Figliuolo, Letícia; Cunha, Simone Carvalho Santos; Moreira, Clarissa; de Souza, Heloisa Justen Moreira (Acta Scientiae Veterinariae, 2018)
Background: Sutures plays an important role in wound repair by providing hemostasis and support for healing suture. Synthetic non-absorbable like polypropylene suture materials induce minimal tissue reaction. Polypropylene has not been associated to neoplasms in domestic animals. The aim this study is to describe the first case of polypropylene suture induced hemangiosarcoma in an abdominal wall of a feline. Case: A 13-year-old female domestic shorthair cat was presented with a ventral abdominal subcutaneous mass. Clinical examination revealed a firm, rough, and irregular, approximately 6 x 4 cm subcutaneous mass involving the caudal ventral abdomen. A complete blood (cell) count (CBC) was within normal limits. Leukemia and FIV tests were negative; and the results of a chemistry panel revealed elevated creatinine (valor: 2.0 reference range: 0.5-1.9). Abdominal ultrasound revealed a large mass of mixed echogenicity in the mid-ventral abdomen cranial to the bladder, measuring approximately 6 x 4 cm in the middle line with suture deeply embedded within mass suggesting foreign body reaction or neoplasm. There was evidence of sutures (hyperechoic lines) along the caudal abdominal wall extending into the mass. Records indicated that ovariohysterectomy procedure was performed 12 years previously at the same clinic and the closure of the abdominal wall was made with polypropylene sutures. No other abdominal surgery was performed in this cat. A fine-needle aspirate of the mass and contrast-enhanced computed tomography was not performed due to owner’s finance restrains. The cat was referred to surgery and the mass was excised. No evidence of metastasis was noted during surgery. Histologically, the neoplastic cells were oval to round with granular cytoplasm and vesicular nucleus and exhibited moderate cellular and nuclear pleomorphism. A diagnosis of abdominal wall hemangiosarcoma was made with suture deeply embedded within mass. Surgical margins were clear. Chemotherapy was indicated, but the owner declined due to financial reasons. This is the first polypropylene suture mass associated hemangiosarcoma in cats. Discussion: Hemangiosarcoma is a malignant neoplasm of vascular endothelial cells origin and it may be associated with chronic inflammation and neoplastic transformation. It was reported in previous studies, and it could be a hypothesis for the presented clinical case. There are two cases described in the literature of abdominal wall tumor associated with foreign body and exuberant inflammatory response in cats using different types of suture; one case is a steel staple developing hemangiosarcoma and the other is polyester sutures developed fibrosarcoma. The present study shows a primary hemangiosarcoma diagnosed several years after closure of abdominal wall using polypropylene sutures in a female cat. Polypropylene is a monofilament suture that create less tissue-drag and induces less inflammation than multifilament sutures and is the preferred suture to close abdominal wall. Cats demonstrate a peculiar predisposition to neoplasms at the site of injury. Although the pathogenesis is still unclear, the introduction a “foreign body” may cause inflammatory process that act as a stimulus to neoplasia formation. We believe that polypropylene was the foreign material that may have played a role in tumor development in this case and it has not been reported before. Polypropylene sutures were found on gross examination of excised material. Any uncoated braided non-absorbable material located deeply in tissues may evoke a chronic inflammatory response (granuloma). A granuloma may evolve to malignancy in some cats. Despite polypropylene materials induce minimal tissue reaction, it may be associated to neoplasm. Keywords: polypropylene suture, hemangiosarcoma, cat, tumor induced by foreign body.